العلاقة بين القلق اللغوي ومهارة الكلام لدى طالبات المستوى الأول العالي (أ) بمعهد دار اللغة والدعوة - Alvia Putri Prima Sari; Nur Rif'ah; Ahmad Nahid Mashury (Program Studi Pendidikan Bahasa Arab, 2026)
This study aimed to investigate the relationship between language anxiety and speaking skills among first-year female students of Class A at Darullughah Wadda’wah Islamic Boarding School. In learning a foreign language, many students experience language anxiety, especially when speaking in front of the class, which may be associated with their speaking performance. This study employed a quantitative correlational design involving 37 students as the research sample. Data were collected through the Foreign Language Classroom Anxiety Scale (FLCAS) questionnaire to measure language anxiety and an oral speaking test to assess speaking skills. The data were analyzed statistically using correlation and multiple regression analysis with Microsoft Excel, while Cronbach’s Alpha was used to test the reliability of the instrument. The findings revealed a statistically significant relationship between language anxiety and speaking skills, with a correlation coefficient of 0.611 and a significance value of 0.001. The results also showed that test anxiety was the only dimension that reached statistical significance, while communication anxiety and fear of negative evaluation were not statistically significant. These findings indicate that language anxiety is associated with students’ speaking performance in learning Arabic.